Analysis of argumentations of selected Czech political parties regarding the euro adoption - Nosák, David Ivan; Kašparová, Eva, 1958-; Zedník, Jan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
The aim of this thesis is to perform a qualitative content analysis of argumentations of selected Czech political parties regarding the adoption of the euro in the Czech Republic. In the first part, the thesis gives an overview of different dimensions of arguments that can be used when referring to the euro adoption with respect to the situation in the Czech Republic. It refers to academic and expert data from independent individuals or institutions and presents positions that speak both “for” and “against” the euro adoption, in order to give an objective view on the topic. In the practical part, the thesis analyzes concrete argumentations of selected political parties based on the data collected and the dimensions of arguments identified in the first part.
Vedoucí práce: Eva Kašparová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses